Effects of Development and Ripening Stage on Phytochemical Compositions, Antioxidant and Antibacterial Activities of Date Palm Fruits - Bentebba, F.Z.; Ghiaba, Z.; Saidi, M.; Bensasi, C. (Asian Journal of Chemistry, 2019)
Edible parts of two dates cultivars (Deguel ahmar and Tanslit) at four maturation stages khellal, besser, rutab and tamr were analyzed for their phytochemical composition (total phenolic, total flavonoid and condensed tannins contents) as well as antioxidant and antibacterial activities. The antioxidant activity evaluated in vitro using scavenging assays of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical and ferric reducing power. Antibacterial activity of extracts were evaluated in vitro by the agar disk diffusion method against five pathogenic bacterias trains: Bacillus subtilis ATCC 6633, Enterococcus ATCC 3315, Staphylococcus aureus ATCC 43300, Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 7320. Results suggested that the content of these phytochemicals are very important at khellal stage and then decreased during maturation followed by a decrease in the antioxidant activity.